Glamour Through the Prism of Deconstructivism - Budіak, Victoria (HUDPROM: The Ukrainian Art and Design Journal, 2025)
The article examines the synthesis of two seemingly opposing forms – order and “disorder” – in the fashion system, manifested through the simultaneous application of glamorization and deconstruction within a single design product. At first glance, this appears as an incompatible combination: on the one hand, chaos, as the foundation of deconstruction, is associated with the disruption of binary oppositions and the overcoming of rigid hierarchical systems of classification and language; on the other hand, glamour is linked to fixed signs and stable characteristics. Yet one key concept unites them – shocking effect. In the fashion system, the method of deconstruction acquires additional meaning: it addresses the idea of novelty, a mechanism of resistance and a practice of breaking linear chronological continuity. At the same time, illusory disorder and apparent chaos do not signify the absence of structure. The concept of deconstructivism in glamour suggests a specific mode of content formation, distinct notions of demarcation between primary and secondary, as well as between center and periphery. On this basis, the article argues that the relevance of the issue is determined by several factors, including the identification of the main means by which deconstructivism manifests itself in glamour, and the question of primacy – whether it lies in the form-giving design of an object or in its internal content, expressed through construction techniques, decoration, and embellishment. The study reflects how deconstructivism influences the form, cut, and ornamental elements of glamorous costume. Based on the analysis of the work of leading designers and brands, the article reveals the role of deconstructivism in a glamorous costume. It also identifies the fabrics and materials most closely aligned with the concept and most in demand among contemporary fashion designers.